Review: A State-of-the-Art of Time Complexity (Non-Recursive and Recursive Fibonacci Algorithm) - Cholissodin, Imam; Riyandani, Efi (Journal of Information Technology and Computer Science, 2016)
Abstract. Solving strategies in the computation the time complexity of an algorithm is very essentials. Some existing methods have inoptimal in the explanations of solutions, because it takes a long step and for the final result is not exact, or only limited utilize in solving by the approach. Actually there have been several studies that develop the final model equation Fibonacci time complexity of recursive algorithms, but the steps are still needed a complex operation. In this research has been done several major studies related to recursive algorithms Fibonacci analysis, which involves the general formula series, begin with determining the next term directly with the equation and find the sum of series also with an equation too. The method used in this study utilizing decomposition technique with backward substitution based on a single side outlining. The final results show of the single side outlining was found that this technique is able to produce exact solutions, efficient, easy to operate and more understand steps. Keywords: Time Complexity, Non-Recursive, Recursive, Fibonacci Algorithm